2010
DOI: 10.1063/1.3483617
|View full text |Cite
|
Sign up to set email alerts
|

Light emission from silicon/gold nanoparticle systems

Abstract: Photoluminescent nanostructured semiconductor/metal systems consisting of silicon nanocrystals and gold nanoparticles are obtained by gold-catalyzed chemical etching. The interplay between silicon and gold nanostructures is investigated by photoluminescence spectroscopy upon continuous and pulsed excitation, both at room and low temperature. Comparison with reference samples, obtained removing gold particles by selective etching, highlights an enhanced emission in samples containing silicon and gold nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 20 publications
0
14
1
Order By: Relevance
“…We suggested that the origin of this band comes from the exciting laser that penetrated through the porous layer and directly exciting throughout AuNPs. Optical coupling between them is claimed to govern the observed behavior [19,20]. Meanwhile, the sample deposited with 3.5 mA/cm 2 (sample c) had almost no PL peak that it is not included in the figure.…”
Section: Resultsmentioning
confidence: 99%
“…We suggested that the origin of this band comes from the exciting laser that penetrated through the porous layer and directly exciting throughout AuNPs. Optical coupling between them is claimed to govern the observed behavior [19,20]. Meanwhile, the sample deposited with 3.5 mA/cm 2 (sample c) had almost no PL peak that it is not included in the figure.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, SPR of Au nanoparticles can be utilized to enhance emission of semiconductors nanoparticles. The ability of noble metals to modify the optical properties of Si has already been demonstrated and a remarkable enhancement in the radiative emission rate has been reported [2]. Furthermore, semiconductor nanowhiskers normally require seed particles, often Au nanoparticles, to grow via the vapor-liquidsolid mechanism.…”
Section: Motivation and Synthesis Approachmentioning
confidence: 98%
“…First demonstrated for producing films from monodisperse, monocrystalline PbS nanoparticles [11], the basic concept is (1) to synthesize the particles by means of a physical synthesis step forming a polydisperse nanoaerosol, (2) to select a small portion of the size spectrum by means of electrical mobility-based size fractionation in a Differential Mobility Analyzer (DMA), (3) to convert the aggregated and irregularly shaped nanoparticles into quasi-spherical and monocrystalline particles by means of in-flight thermal annealing and (4) to deposit the nanoparticles on suitable substrates. Clearly, this approach has the disadvantage of losing a large fraction of the originally synthesized particles.…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement of photoluminescence (PL) intensity in Si nanomaterials has been reported by several research groups. [13][14][15][16][17][18][19][20][21][22][23][24] Biteen et al first reported local-field-enhanced light emission from a silicon nanomaterial using a noble metal nanostructure, and they quantified the PL-intensity enhancement factor (EF) to be 40. 18 Nychyporuk et al reported the EF of Si-QDs to be 60 using a monolayer of silver (Ag) nano-islands; this EF of 60 is the largest EF obtained to date for Si-QDs.…”
Section: Introductionmentioning
confidence: 99%